The albumin-bilirubin (ALBI) grade as a significant prognostic factor in colorectal cancer patients with liver metastases - Demircan, Nazım; Köstek, Osman; Gökyer, Ali; Küçükarda, Ahmet; Hacıoğlu, Muhammet; Erdoğan, Bülent; Uzunoğlu, Sernaz; Çiçin, İrfan (Journal of Surgery and Medicine, 2019)
Aim: Colorectal cancer is one of the most common cancers and liver metastases are frequent during its course. Albumin-bilirubin (ALBI) score/grade was shown to predict survival in hepatocellular carcinoma. We aimed to assess the prognostic value of the ALBI score/grade in colorectal cancer patients with liver metastases. Methods: Medical records of patients with colorectal cancer and synchronous or metachronous liver metastases were reviewed. Serum albumin, total bilirubin, lactate dehydrogenase, carcinoembryogenic antigen and neutrophile-to-lymphocyte ratio at the time of first liver metastasis were determined. ALBI score was calculated from serum albumin and bilirubin and was graded. Multivariate regression models were used to evaluate prognostic factors. Results: The study included 223 patients. Median overall survival was 23.9, 16.0 and 4.0 months for ALBI grades 1, 2 and 3, respectively (P<0.001). In the first multivariate model, serum albumin was an independent prognostic factor (Hazard ratio=1.97, P=0.001) but total bilirubin was not (Hazard ratio=1.43, P=0.17). In the second multivariate analysis, ALBI grade was a significant predictor of overall survival (Hazard ratio=1.54, P=0.02 for ALBI grade 2 and Hazard ratio=3.85, P<0.001 for ALBI grade 3). Conclusion: ALBI grade may be a valuable prognostic method to estimate the mortality of patients with colorectal cancer and liver metastases.